The Intrinsic Mutability of Code Poetry Uncovers New Notions of Poetic Design - Alvarez, Christian Iñigo D.L. (Philippine Humanities Review; Vol 19 No 1 (2017), 2018)
The paper focuses on code poetry and the need to extend current literary modes of analysis to accommodate aspects of digital poetry not previously found in written poetry. In the first section, a basic discussion on the difference between written poetry and code is made, which argues that while there are inherent differences between writing poetry and writing code, the syntax of modern programming languages is getting closer and closer to regular English sentences making the code a possible substrate for poetry. The transformative nature of programming languages makes them an interesting substrate. This leads to the question of how one could use current literary frameworks to analyze poetry that’s created using a programming language, bringing with it elements not previously available in written text. What follows is a discussion of Turco’s four levels of poetry, leading up to the extension of the framework with the addition of a fifth level--”the event level,” which seeks to take into account the additional features of the digital substrate without breaking the existing modes of analysis of the written text. KEYWORDS: digital poetry, code poetry, electronic literature, new media, programming languages